Analysis of Industrial Practice Problems in Automotive Students - Suyitno Suyitno; Bambang Sudarsono; Dwi Jatmoko (Jurnal Taman Vokasi, 2019)
Abstracts. The objectives of this study include 1) analyzing the problems of industrial practice by students, and 2) strategies to improve the quality of industrial practice of students with educational autonomy techniques. The method in this research is descriptive research with cluster random sampling technique. The selection of this population is the entire University in Central Java, namely the Veterans University of Semarang and Muhamamdiyah Purworejo University and Yogyakarta namely the Sarjanawiyata Tamansiswa Yogyakarta University. From the results of the questionnaire distributed, it turns out that 53% stated that the study program in general did not prepare the practice first before leaving for Industrial Practice. There are 18% of students who are not serious in carrying out industrial practices in industrial sites, and there are 24% of disciplines that are reduced after industrial practices. In addition there are 12% who do not understand the flow of industry practice and 6% of difficulties in making reports. From the questionnaire above stated that 57% of the shortcomings of managing industrial practices is the absence of an agreement between the competencies that must be studied in the study program and those that will be learned in the industry. There are a number of steps that must be taken in improving the quality of industrial practices, he said, by 75% stating that there must be an update in learning in the industry, 83% should have guidelines for learning industrial practices, for 67% there are guidance for guidance for instructors in the field, amounting to 75% there are guidance guidelines for supervisors who conduct guidance to the industry.